Simultaneous Estimation of Metoprolol Succinate and Lacidipine in Binary Combination using High Performance Liquid Chromatographic Method - jain, Deepak; Jain, Nilesh; Jain, Ruchi; Patel, Preeti; Patel, Vijay; Jain, Surendra (Jordan Journal of Pharmaceutical Sciences, 2016)
A simple, reliable, rapid, precise, sensitive, rugged and validated RP-HPLC method has been developed to determine Metoprolol succinate and Lacidipine in synthetic mixture form. Chromatographic separation achieved isocratically on Prontosil C18 column (5µm, 250mm × 4.60mm) and acetonitrile: 20mM Phosphate buffer (pH 3.6) in the ratio of 60:40 (v/v) as the mobile phase, at a flow rate of 1 mL/min. Detection was carried out at 278 nm. The mean retention times for metoprolol succinate and lacidipine was found to be 5.25±0.5 and 6.72±0.5 min, respectively. No interference was found by the excipients in the synthetic mixture. Linearity for metoprolol succinate and lacidipine was in the range of 5-25μg/mL and 4-20μg/mL, respectively. The mean recoveries obtained for metoprolol succinate and lacidipine were 100.03 and 99.67 % respectively and RSD was less than 2. The correlation coefficients for all components are close to 1. The proposed method was validated in terms of linearity, range, accuracy, precision, specificity, robustness and the method is successfully applies to the estimation of metoprolol succinate and lacidipine in bulk and in a synthetic mixture.